Super (a,d)-H-Antimagic Total Covering of Amalgamation Graph K_4 and W_4 - Anggraeni, Novri; Dafik, Dafik (Prosiding Seminar Matematika dan Pendidikan Matematik, 2014)
A graph G(V,E) has a H-covering if every edge in E belongs to a subgraph of G isomorphic to H. An (a,d)-H-antimagic total covering is a total labeling λ from V(G)E(G) onto the integers {1,2,3,...,|V(G)E(G)|} with the property that, for every subgraph A of G isomorphic to H the A=_vV(A)λ(v)+_eE(A)λ(e) forms an arithmetic sequence. A graph that admits such a labeling is called an (a,d)-H-antimagic total covering. In addition, if {λ(v)}_vV={1,...,|V|}, then the graph is called H-super antimagic graph. In this paper we study of amalgamasi graph K_4 and W_4.